Chemical process design : computer-aided case studies - Dimian, Alexandre C. (Wiley-VCH, 2008)
"This how-to book deals with the challenge of designing sustainable chemical processes by way of systematic methods aided by computer simulation. Its didactic approach guides readers from basic knowledge to mastering complex flowsheets, and is unique in emphasizing the integration of process design and plant wide control at an early conceptual stage. The simulation results are compared with flowsheets and performance indices from real industrial processes, with the complete input data also provided, such that readers are able to reproduce the results with their own simulation. Numerous case studies illustrate genetic creative issues, as well as the efficient use of simulation techniques, with each one standing for an important topic taken from practice. This book is for everyone interested in innovative chemical processes, from undergraduates to professional designers."--BOOK JACKET.